2012
DOI: 10.1007/s11250-012-0226-x
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks of foot-and-mouth disease in Peninsular Malaysia from 2001 to 2007

Abstract: This is a retrospective study of the outbreaks of foot-and-mouth disease (FMD) in Peninsular Malaysia between 2001 and May 2007. In total, 270 outbreaks of FMD were recorded. Serotype O virus (89.95 %) and serotype A (7.7 %) had caused the outbreaks. Significant differences on the occurrence of FMD were found between the years (t = 5.73, P = 0.000, df = 11), months (t = 4.7, P = 0.000, df = 11), monsoon season (t = 2.63, P = 0.025, df = 10) and states (t = 4.84, P = 0.001, df = 10). A peak of outbreaks observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…It is well known that animal and vehicle movements are risk factors that are associated with endemic transmissions [11,28]. As evidenced by various previous studies, the movement of cattle was significantly associated with FMD outbreaks [10,29,30]. Similarly, we found that purchasing a new cow on a farm without observing a quarantine protocol increased the risk of an FMD outbreak by 2.41 times.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It is well known that animal and vehicle movements are risk factors that are associated with endemic transmissions [11,28]. As evidenced by various previous studies, the movement of cattle was significantly associated with FMD outbreaks [10,29,30]. Similarly, we found that purchasing a new cow on a farm without observing a quarantine protocol increased the risk of an FMD outbreak by 2.41 times.…”
Section: Discussionsupporting
confidence: 79%
“…For instance, questionnaire-based case-control studies have been widely used to gather information on the risk factors associated with FMD spread in certain countries. The established risk factors include livestock transportation methods [10], the sharing of grazing areas [11], the proximity of the farm to the main road [12] and the mixing of animals within public pastures [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in certain areas of the world small ruminant represent the main FMD-susceptible livestock and can play an important role for spreading the infection during outbreaks. 8 – 10 …”
Section: Introductionmentioning
confidence: 99%
“…However, the 2010/2011 epidemic was first confirmed in a local small and medium city in GyeongBuk Province and resulted in the largest number of infected animals recorded since the first detection of FMD cases in 1911 (QIA, 2011). In contrast to FMD epidemics in other countries in which movement of the infected animals largely contributed to the spread of the disease (Rweyemamu et al, 2008;Ramanoon et al, 2013), human behaviours were major factors in the spread of the FMD virus in the Korean epidemics of 2010/2011 and 2002 (Wee et al, 2008). Korea was prompted to revise their contingency plan by tailoring it to its unique livestock environment.…”
Section: Discussionmentioning
confidence: 99%